Comparative pharmacokinetics and bioavailability of brimonidine following ocular and dermal administration of brimonidine tartrate ophthalmic solution and gel in patients with moderate‐to‐severe facial erythema associated with rosacea. (16th July 2014) - Benkali, K.; Leoni, M.; Rony, F.; Bouer, R.; Fernando, A.; Graeber, M.; Wagner, N.
Summary Background Persistent facial erythema is the most common primary pathological feature of rosacea, the only treatment for which is brimonidine tartrate (BT) gel. Objectives To assess the relative bioavailability of topical BT gel in comparison with the ophthalmic BT solution. Methods A pharmacokinetic study was conducted to compare intraindividual systemic exposures after dermal application of BT gel (0·07%, 0·18% and 0·5%) under maximal use conditions in patients with moderate‐to‐severe facial erythema associated with rosacea, and administration of BT ophthalmic solution 0·2%. Results Patients who received BT ophthalmic solution 0·2% three times a day for 1 day had a mean Cmax of 54 ± 28 pg mL−1 and a mean 0–24‐h area under the curve (AUC0–24 h) of 568 ± 277 pg h mL−1. Topical application of BT gel for 29 days resulted in quantifiable systemic exposure in 22%, 48%, 71% and 79% of patients who received BT gel 0·07% twice daily, 0·18% once daily, 0·18% twice daily and 0·5% once daily, respectively. The mean Cmax values for the BT gels ranged between 13 and 25 pg mL−1, and mean AUC0–24 h values ranged between 42 and 290 pg h mL−1. Systemic exposure increased with applied dose, with no drug accumulation for the duration of treatment. The systemic exposure observed with the highest dose of BT gel (0·5% once daily) was significantly lower than the systemic levels observed for the ophthalmic solution. 0·2% apply for all the concentrations. Conclusions The systemic safety profile of BT gel may be considered better than that of the ophthalmic solution.